Factors Influencing Participation In Professional Developmental Activities Among Nursing Personnel - Silwal, Rojeena; Panta, Sarita (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Professional Developmental Activities (PDA) are the means to update the health care providers with new knowledge and help them to provide quality care and better patient outcomes. This study aims to determine the factors that influence participation in professional development activities among nursing personnel. Methods: A cross sectional study was conducted among nurses in Tribhuvan University Teaching Hospital, Maharajgung, Kathmandu, Nepal. Simple random sampling technique was used to collect data. Data was collected through self-administered semi-structured questionnaire. The collected data were analysed for descriptive and inferential statistics using SPSS version 20.Results: Total 124 nurses participated in the study. Most (88.7%) were working as a staff nurse. Majority (60.5%) of nurses had participated in PDA within last 12 months. The most common factors which motivated nurses to participate in PDA were family / spouse support and improve knowledge (98.7%). The major hindering factors were shortage of staff (97.9%), and lack of cost (91.8%). Chi-square and Fisher exact tests were used to test the association of selected variables and PDA participation and significant association was seen between participants designation categorised as staff nurse, senior staff nurse and nursing in charge (p < 0.008) and those who were involved in professional developmental activities.Conclusions: Based on findings, the study concluded that there are several factors either hindering or motivating related to work, family, financial, personal and career that contributes to nurses participation in PDA.